1991
DOI: 10.2307/1242434
|View full text |Cite
|
Sign up to set email alerts
|

The On‐Farm Costs of Reducing Groundwater Pollution

Abstract: Agricultural chemicals ate a source of groundwater pollution in some areas. Regulatory options to reduce such nonpoint pollution imply costs to producers. By integrating plant simulation, hydrologic, and economic models of farm-level processes, this study evaluates on-fama costs of strategies to reduce nitrate groundwater pollution. The empi¡ focus is on intensively managed, irrigated farms in the Columbia Basin of Oregon. Results suggest that changes in timing and application rates of nitrogen and water reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(47 citation statements)
references
References 12 publications
6
41
0
Order By: Relevance
“…The fact that fertilizer application could be decreased-in some cases significantly-without adversely affecting crop yields indicated both the substantial amounts of P and potassium in the soil of many farms from past applications as well as inefficient use of fertilizer nutrients. This crop yield result is consistent with past studies, which have found that reduction in nitrogen fertilizer application can be accomplished without negative economic consequences (Johnson et al 1991;Randhir and Lee 1997). One of the outcomes of the MAEAP for Michigan livestock producers was more awareness of the importance of efficient manure utilization consistent with other studies (e.g., Ribaudo et al 2004).…”
Section: Programsupporting
confidence: 89%
“…The fact that fertilizer application could be decreased-in some cases significantly-without adversely affecting crop yields indicated both the substantial amounts of P and potassium in the soil of many farms from past applications as well as inefficient use of fertilizer nutrients. This crop yield result is consistent with past studies, which have found that reduction in nitrogen fertilizer application can be accomplished without negative economic consequences (Johnson et al 1991;Randhir and Lee 1997). One of the outcomes of the MAEAP for Michigan livestock producers was more awareness of the importance of efficient manure utilization consistent with other studies (e.g., Ribaudo et al 2004).…”
Section: Programsupporting
confidence: 89%
“…Land use regulation or voluntary arrangements within buffer zones could offer health and environmental benefits of reduced groundwater nitrate concentrations along with net revenue gains. Land use buffer policies, accompanied by model informed land use planning, could integrate improved management practices, low-or no-input crop types, and/or alternative treatment or prevention options that would serve to decrease NO3 leaching rates within buffer zones while still providing economic benefit [57].…”
Section: Beneficial Agricultural Management Practices In Buffer Zonesmentioning
confidence: 99%
“…Farm economic models such as WFM (Beukes 2005) can estimate the potential profits from different land use and management options. Rather than independent agroecological and agro-economic models, integrated agro-ecological and agroeconomic models which can predict both the nitrate losses and potential profits from alternative land uses (Johnson, 1991;Mohamed et al, 2000) would better help the farms in optimizing their bids. But, the assessment of potential profit is a private matter and the farms will have to be responsible for their own judgments irrespective of the model used.…”
Section: Farm Profit Functionsmentioning
confidence: 99%